Constipation, ileus and medication use during clozapine treatment in patients with schizophrenia in Iceland. (3rd October 2018) - Ingimarsson, Oddur; MacCabe, James H.; Sigurdsson, Engilbert
Abstract: Purpose of the article: Clozapine is the only evidence based treatment for treatment-resistant schizophrenia. Constipation is a well known side effect of clozapine treatment. The aims of this study are to describe the prevalence of constipation and ileus during clozapine treatment of patients with schizophrenia in Iceland and to assess the concomitant use of medication that can cause constipation, and laxatives used to treat constipation. Materials and methods: We identified 188 patients treated with clozapine by searching the electronic health records of Landspitali, the National University Hospital, during the study period 1.1.1998 – 21.11.2014. Cases of constipation and ileus were identified using an electronic search with keywords related to ileus in the patients' electronic health records. Detailed medication use was available for 154 patients that used clozapine for at least one year. Results: Four out of 188 patients were diagnosed with ileus that resulted in admission to hospital. Two of these required a permanent stoma as a consequence of their ileus. Laxatives were prescribed for 24 out of 154 patients (15.4%) while on clozapine. In total 40.9% of the patients either had laxatives prescribed or had constipation documented in the medical records. Apart from clozapine, other medications known to cause constipation were prescribed to 28 out of 154 patients (18.2%). Conclusions: Constipation is a common problem during clozapine treatment which can progress to full-blown ileus which can be fatal. Clinicians need to monitor signs of constipation during treatment with clozapine and respond to it with lifestyle advice and laxative treatment.